Inisiasi Pembekalan Beladiri Praktis Sebagai Sarana Non-Penal Terhadap Ancaman Kekerasan Seksual di Lingkungan Kampus - Supanto Supanto; Sauzan Vidya Rastratama Mitra; Indriya Ramadhan; Debrio Daffa Abroor; Kanez Pravangastha; Alfi Suryo Koesum (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The threat of sexual violence in Indonesia, which is getting worse day by day, has become an urgency for all levels of society in Indonesia. Inappropriate legal interpretations in society often raise big question marks about the protection of victims of sexual violence. Therefore, how is forced defense (noodwear) implemented as a reason for abolition of criminal penalties in Indonesia? At the same time, how is Article 49 paragraph (1) of the Criminal Code applied to crimes of morality? To solve this problem, it is not only the government that must intervene. However, people must also have self-defense, for example through practical self-defense movements that can protect themselves, but do not kill the perpetrator so that the victim does not go too far in defending himself. How to implement practical self-defense movements in an effort to protect victims of sexual violence? This is the problem we will examine to provide a solution. In this way, it is hoped that this effort will be able to produce an in-depth study regarding the protection of victims of sexual violence and how to apply practical self-defense to protect themselves when victims experience an act of sexual violence.